Duplex stainless steel fabricated by selective laser melting - Microstructural and mechanical properties. (5th November 2017) - Hengsbach, Florian; Koppa, Peter; Duschik, Kristina; Holzweissig, Martin Joachim; Burns, Madison; Nellesen, Jens; Tillmann, Wolfgang; Tröster, Thomas; Hoyer, Kay-Peter; Schaper, Mirko
Abstract: In the scope of the present study, microstructural and mechanical characterizations of duplex stainless steel UNS S31803 processed by selective laser melting (SLM) are conducted. The findings shed light on the phase arrangement evolving in the as-built condition and in several heat-treated conditions. In the as-built condition, austenite formation is almost suppressed due to process-related high cooling rates. Therefore, several heat treatments ranging from 900 °C to 1200 °C for 5 min each were performed in order to adjust to the desired austenitic-ferritic microstructure. Results generated by transmission electron microscopy (TEM) reveal a high dislocation density induced during SLM fabrication, such that a recrystallized microstructure prevails after the heat treatment. Tensile tests display the severe impact of the heat treatment on the resulting mechanical response. The nearly complete ferritic as-built specimens obtain a higher ultimate tensile strength and a reduced elongation at fracture compared to the heat-treated specimens. Graphical abstract: Highlights: Successful fabrication of duplex stainless steel via selective laser melting is reported. A nearly balanced austenite-ferrite arrangement is obtained after suitable heat treatment. High dislocation density in the as-built condition provokes recrystallization during further heat-treatment.